Analyzing the active audience: Reluctant, reactive, fearful, or lazy? Forms and motives of participation in mainstream journalism - Spyridou, Lia Paschalia (My University, 2019)
Participation has become a key issue in contemporary journalism studies, yet research on how the participatory space is being appropriated by users is rather limited. This article attempts a methodological contribution by offering a way to analyze participatory journalism in reference to variant participatory affordances enabling different levels of creative effort, control, and editorial permeability. To do so, it understands participation as the active involvement of users, and makes an analytical connection among technological affordances, motivations, and contextual factors. The article offers empirical evidence challenging both cyber-optimist and cyber-pessimist assumptions about participation. Drawing on insights from a web-based survey, it is argued that the ‘reluctant audience’ paradigm may be interpreted in terms of the ‘lazy audience’ and the ‘fearful audience’, which seem to coexist along with the ‘reactive audience’.
Keywords: active audience; participatory journalism; user-generated content; participatory tools